A meta-analysis of the effects of strength training on arterial stiffness - Pablo García-Mateo; Rodrigo Ramirez-Campillo; Antonio García-; Manuel Antonio Rodríguez-Pérez (Termedia Publishing House, 2022)
Purpose Arterial stiffness (AS) describes the mechanical properties of the arterial wall and predicts cardiovascular health. Even if it is known that AS is improved by aerobic exercise, the effects of resistance training (RT) are less clear. Therefore, this meta-analysis aimed to assess the effects of RT on AS. Methods A systematic search for randomized controlled trials published until October 2020 was performed in the PubMed, SPORTDiscus, MEDLINE, and Web of Science databases. Overall, 19 studies were selected, with 12.58 ± 0.82 methodological quality points (from a total 15 points) and a total of 626 participants. Results No significant long-term effect was noted for RT on AS ( ES = -0.07; 95% CI: -0.59 to 0.45; p = 0.789). However, RT induced a significant acute increase in AS ( ES = 1.07; 95% CI: 1.55 to 0.59; p < 0.001). No other factors (i.e., age, gender, AS measurement, upper- vs. lower-body RT, training intensity, duration, frequency) had a significant modifying effect on AS in acute or long-term interventions. Conclusions Although RT induces an acute AS increase, this effect has no long-term impact, irrespective of the participant's age, sex, or RT variables, such as intensity. However, the clinical implications of acute AS increase after RT are unknown.